2011
DOI: 10.1155/2011/867493
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Emergence and Survival of Mutations Using a Self Regulating Multitype Branching Processes

Abstract: It is difficult for an experimenter to study the emergence and survival of mutations, because mutations are rare events so that large experimental population must be maintained to ensure a reasonable chance that a mutation will be observed. In his famous book, The Genetical Theory of Natural Selection, Sir R. A. Fisher introduced branching processes into evolutionary genetics as a framework for studying the emergence and survival of mutations in an evolving population. During the lifespan of Fisher, computer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As demonstrated in recent publications, Mode and Sleeman [9], Mode et al (2011), [12,13], by deriving formulas for the conditional expectation of any random variable at time , given the evolution of the process prior to , it is possible to derive a set of recursive nonlinear difference equations, such that, given the initial values of the random functions at time = 0, estimates of the sample functions of the process can be derived for all > 1. In previous publications dating back at least a decade, this derived set of equations has been called the deterministic model embedded in the stochastic process under consideration.…”
Section: An Embedded Deterministic Model In An Age-structured Stochasmentioning
confidence: 91%
See 2 more Smart Citations
“…As demonstrated in recent publications, Mode and Sleeman [9], Mode et al (2011), [12,13], by deriving formulas for the conditional expectation of any random variable at time , given the evolution of the process prior to , it is possible to derive a set of recursive nonlinear difference equations, such that, given the initial values of the random functions at time = 0, estimates of the sample functions of the process can be derived for all > 1. In previous publications dating back at least a decade, this derived set of equations has been called the deterministic model embedded in the stochastic process under consideration.…”
Section: An Embedded Deterministic Model In An Age-structured Stochasmentioning
confidence: 91%
“…More precisely, the components of the vector are Z ( ; , ) = ( ( ; , , 1) , ( ; , , 2) , ( ; , , 3)) . (13) Observe for each = 1, 2, 3 the elements in the vector ( ; , , ) for = 1, 2, 3 are the random number of females of genotype and age that have sexual contacts with a males of genotype . Altogether there are 9 types of sexual contacts when there are 3 genotypes of each sex as was shown in the previous section.…”
Section: Births In a Two Sex Age Dependent Population Process Withoutmentioning
confidence: 99%
See 1 more Smart Citation
“…For if more than three types are considered in a computer simulation experiment, then it is more difficult statistically to provide informative summarizations of samples of simulated data than if only three types are considered in an experiment. If a reader is interested in other illustrative experiments using the three type model of chapter 10, it is suggested that Mode et al (2011b) be consulted.…”
Section: Overview Of Book's Contentsmentioning
confidence: 99%
“…While carrying out the computer experiments reported in the book, it was not observed that a rare beneficial mutation would fail appear in the population, using the self regulating process three type branching process under consideration. But if a reader is interested in experiments using this model such that an advantageous mutant genotype did not appear in the population in experiment completed after work on the book was finished, the recent paper of Mode et al (2011b) may also be consulted, where other experiments in which the predictions of the embedded deterministic model are not consistent with those of the process.…”
Section: An Example In Which the Predictions Of Embedded Determinimentioning
confidence: 99%